PERATURAN HUKUM TERKAIT TANGGUNG JAWAB PJI DALAM PENYARINGAN KONTEN PORNOGRAFI MELALUI INTERNET DI INDONESIA - Akbar, Gitacitra Purnama; Wantu, Fence M.; Ismail, Dian Ekawaty (The Juris, 2023)
Nowadays, the development of science and technology such as the Internet (interconnected computer network) can practically support any profession and its work, thus allowing you to achieve your life goals in a short time. The internet can also be detrimental to the interests of others. As internet and mobile phone technology advances, so does social media. As the number of internet users increases, more and more people are using these social networks for various purposes, some for positive purposes, some for cybercrime. The ease of access to pornographic content is believed to be one of the main causes of the increase in sexual crimes against children in Indonesia. The research used is normative legal research that examines literature studies based on normative systems. The results of this research are in the form of an analysis of the legal regulations related to the responsibility of PJI in filtering pornographic content via the internet in Indonesia.